PENEGAKAN HUKUM TERHADAP PENCEMARAN LINGKUNGAN AKIBAT TAMBANG BATU BARA (STUDI KASUS PUTUSAN PN NOMOR 10/PDT.G/2018/PN) - Yemima Nurhaida Sryagnes Batubara; Lamtiurma Sinaga, Fajar Tri Kesuma, Sari Sesilia Depari, Risa Elvina Nasution, Bella Natasiya (JOURNAL OF LAW AND NATION, 2024)
Environmental pollution due to coal mining is a serious problem in Indonesia. Environmental pollution due to coal mining occurs because mining activities do not comply with the harmony of the ecosystem in the environment. The problem is how to enforce the law regarding environmental pollution caused by coal mining, what impacts it causes and how effective law enforcement is. That the defendant has violated the law by carrying out acts of pollution and destruction of the environment. Defendants may be required to be responsible for environmental losses caused by their activities, and may be subject to sanctions in accordance with applicable regulations. The impact of mining activities causes environmental pollution for the plaintiff who suffers both material and immaterial losses. The effectiveness of law enforcement has not been effective because the plaintiff's lawsuit was not accepted by the panel of judges, but it is clear that there has been water, air and noise pollution caused by coal mining.